2017
DOI: 10.1093/jtm/taw101
|View full text |Cite
|
Sign up to set email alerts
|

Travel-acquired ESBL-producing Enterobacteriaceae: impact of colonization at individual and community level

Abstract: Background: Antibiotic resistance is a rapidly increasing global emergency that calls for action from all of society. Intestinal multidrugresistant (MDR) bacteria have spread worldwide with extended-spectrum beta-lactamase (ESBL) -producing Enterobacteriaceae (ESBL-PE) as the most prevalent type. The millions of travelers annually visiting regions with poor hygiene contribute substantially to this spread. Our review explores the underlying data and discusses the consequences of the colonization. Methods: PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(74 citation statements)
references
References 55 publications
6
64
0
4
Order By: Relevance
“…The impact of travel on the global spread of multidrug-resistant E. coli is well documented. Of travelers returning from the Indian subcontinent and Southeast Asia, Africa or South Asia, 20-80% are colonized by MDR-GN bacteria, most commonly ESBL-Ec [8][9][10][11][12][13][14][15]. This colonization can extend over a period of months or even over a year [8,12,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of travel on the global spread of multidrug-resistant E. coli is well documented. Of travelers returning from the Indian subcontinent and Southeast Asia, Africa or South Asia, 20-80% are colonized by MDR-GN bacteria, most commonly ESBL-Ec [8][9][10][11][12][13][14][15]. This colonization can extend over a period of months or even over a year [8,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The literature shows international travel to be strongly associated with acquisition of MDR-GN strains, mostly ESBL-Ec [8][9][10][11][12][13][14][15]. The carriage rate of intestinal MDR-GN bacteria is highest among inhabitants of the Indian subcontinent and Southeast Asia, followed by Africa and South America [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies have found previous antibiotic use to be associated with drug-resistant bacteria carriage in both primary care patients and healthy populations [18,19]. Also, traveling to developing countries has been identified as a risk factor for acquiring drug-resistant bacteria [20]. Risk factors related to healthcare-associated infections (HAI) have been reported as well, including admission to the intensive care unit (ICU), use of catheter, and dialysis [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The Western Pacific, Southeast Asia and Eastern Mediterranean regions have the highest burden of resistance, with more than 60% of AMR carriage occurring via Thailand and India [16]. These popular destinations, as well as the Middle East, have high rates of extended spectrum beta-lactamase (ESBL) resistance, one of the most commonly acquired resistance mechanisms worldwide [17]. The rapid emergence of drug-resistant Candida auris has gained international attention with outbreaks in healthcare facilities around the world, including in patients within Victoria and New South Wales in Australia who acquired the infection from overseas hospitals [18].…”
Section: Introductionmentioning
confidence: 99%